2015
DOI: 10.2298/tsci120718053p
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of mixed convection heat transfer in lid-driven cavity utilizing nanofluid: Effect of type and model of nanofluid

Abstract: Numerical investigation of the laminar mixed convection in two-dimensional lid driven cavity filled with water-Al2O3, water-Cu or water-TiO2 nanofluids is done in this work. In the present study, the top and bottom horizontal walls are thermally insulated while the vertical walls are kept at constant but different temperatures. The governing equations are given in term of the stream function-vorticity formulation in the non-dimensionalized form and then solved numerically by second-order cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…3 and ∆Τ = T h -T c from this table are substituted into eq. (19) to calculate total vertical wall heat transfer. The results are presented in tab.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 and ∆Τ = T h -T c from this table are substituted into eq. (19) to calculate total vertical wall heat transfer. The results are presented in tab.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have also studied nanofluid mixed convection heat transfer in a cavity with moving walls [11][12][13][14][15][16][17][18][19]. Among them, Tiwari and Kumar Das [15] studied the effects of nanoparticles volume fraction and Richardson number for three different moving conditions of the walls and showed that with the increase of nanoparticles volume fraction average Nusselt number of moving walls increases, and from this result they concluded that heat transfer from the walls increases.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of convective heat transfer in lid-driven cavities filled with nanofluids have been reported in recent years [9][10][11][12][13]. What is prevalent in most of the mentioned numerical study on nanofluid combined convection problems is the use of the Brinkman [14] viscosity model for a nanofluid and hence, predict enhancement of heat transfer because of the presence of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…However, for small Richardson number, the Pak and Cho model shows a reduction in the average Nusselt number in the single-lid driven cavity con guration. Pourmamoud et al [36] presented a numerical study on mixed convection uid ow and heat transfer inside a cavity lled with nano uid. They examined the e ect of type and used model in their investigation.…”
Section: Introductionmentioning
confidence: 99%